Nilai-Nilai Kearifan Ekologis dalam Legenda-Legenda Nusantara: Kajian Ekokritik: Ecological Wisdom Values in Indonesian Legends: An Ecocritical Study - Melia Mardi; Yetty Morelent; Syofiani Syofiani (Information Technology and Science(ITScience), 2026)
The increasingly massive global ecological crisis demonstrates the need to strengthen environmental awareness and literacy in society. Various forms of environmental damage, such as the exploitation of natural resources, loss of biodiversity, and ecosystem pollution, are caused not only by technical factors but also by humans' anthropocentric perspective on nature. In this context, oral literature, particularly Nusantara legends, has the potential as a medium for ecological education because it contains local wisdom values regarding the harmonious relationship between humans and the environment. This study aims to describe the forms of ecological wisdom contained in Nusantara legends through an ecocritical perspective. The study uses a descriptive qualitative approach with a content analysis technique. The research data source is a collection of Nusantara legends compiled by Astri Damayanti in the book Kumpulan Legenda Nusantara. The research data consists of words, phrases, sentences, and discourses that represent the relationship between humans and nature, conservation practices, environmental ethics, and natural resource management. The analysis is carried out through heuristic and hermeneutic readings to uncover the explicit and implicit ecological meanings in the text. The results of the study indicate that Nusantara legends contain five main dimensions of ecological wisdom, namely: (1) integration of human and natural life cycles, (2) local conservation wisdom, (3) environmental ethics, (4) warnings against the destructive consequences of natural exploitation, and (5) knowledge of environmental management. These findings indicate that Nusantara legends not only function as cultural heritage but also as ecological educational media that build ethical awareness and human responsibility towards environmental sustainability.